In-Vivo Evaluation Of Carvedilol-?ÄÔÇÖ-Cyclodextrin Inclusion Complexes - Vijaya Kumar, G (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTCarvedilol (BCS Class II drug) is a nonselective ?Ä??-adrenergic blocking agent with ?Ä??1-blocking activity having poor oral bioavailability. The objective of this study is to enhance the oral bioavailability of carvedilol. To improve oral bioavailability of carvedilol, carvedilol ?Ä??-Cyclodextrin complex were formulated by employing the kneading method with the drug: complexing agent1:2. The complexes and pure drug were subjected to pharmacokinetic studies in rabbits. The plasma samples were analyzed by LC-MS/MS method. Various pharmacokinetic parameters were calculated. Carvedilol ?Ä??-Cyclodextrin complex showed higher Ka, AUC values compared with pure drug. Carvedilol ?Ä??-Cyclodextrin complex showed 1.78 fold increases in extent of absorption.